The emerging roles of microbiome and short-chain fatty acids in the pathogenesis of bronchopulmonary dysplasia - Gao, Yuan; Wang, Kaixuan; Lin, Zupan; Cai, Shujing; Peng, Aohui; He, Le; Qi, Hui; Jin, Zhigang; Qian, Xubo (Frontiers in Cellular and Infection Microbiology, 2024)
Bronchopulmonary dysplasia (BPD) is a chronic lung disease that affects premature infants and leads to long-term pulmonary complications. The pathogenesis of BPD has not been fully elucidated yet. In recent years, the microbiome and its metabolites, especially short-chain fatty acids (SCFAs), in the gut and lungs have been demonstrated to be involved in the development and progression of the disease. This review aims to summarize the current knowledge on the potential involvement of the microbiome and SCFAs, especially the latter, in the development and progression of BPD. First, we introduce the gut-lung axis, the production and functions of SCFAs, and the role of SCFAs in lung health and diseases. We then discuss the evidence supporting the involvement of the microbiome and SCFAs in BPD. Finally, we elaborate on the potential mechanisms of the microbiome and SCFAs in BPD, including immune modulation, epigenetic regulation, enhancement of barrier function, and modulation of surfactant production and the gut microbiome. This review could advance our understanding of the microbiome and SCFAs in the pathogenesis of BPD, which also helps identify new therapeutic targets and facilitate new drug development.